Modern weapons and military equipment for issue 1-2019 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2018)
Russia’s MiG-31: A powerful interceptor Mach 3. Current state of the German navy. New plane: an unconscious hunter bombarder of the former SFRY.